The Impact of Blended Learning Approaches on Student Achievement and Motivation in Islamic Religious Education in Australia - Safiyah (https://ejournal.insuriponorogo.ac.id/, 2025)
This study examines the impact of blended learning approaches on student achievement and motivation in Islamic Religious Education (IRE) in Australia. The rapid advancement of educational technology and the increasing integration of digital platforms into classroom instruction have transformed teaching and learning practices across various disciplines, including religious education. Blended learning, which combines face-to-face instruction with online learning activities, has emerged as an innovative pedagogical model capable of enhancing student engagement, flexibility, and academic performance. In the context of Islamic Religious Education, blended learning offers opportunities to create interactive, student-centered, and culturally responsive learning environments that support both cognitive and affective learning outcomes. This study employs a qualitative literature-based approach by reviewing recent scholarly works related to blended learning, student motivation, and academic achievement in religious education settings. The findings indicate that blended learning contributes positively to students’ academic achievement by facilitating access to diverse learning resources, encouraging independent learning, and improving critical thinking skills. Furthermore, blended learning significantly enhances students’ learning motivation through interactive multimedia, collaborative online discussions, and flexible learning environments that accommodate students’ diverse learning needs. However, challenges such as limited technological infrastructure, digital literacy gaps among teachers and students, and difficulties in maintaining students’ spiritual engagement in online settings remain significant concerns. The study concludes that blended learning can serve as an effective instructional strategy in Islamic Religious Education in Australia when supported by adequate technological resources, teacher professional development, and pedagogical innovation. The research also highlights the importance of balancing technological integration with Islamic values and face-to-face spiritual interaction to ensure holistic educational development.